THEORETICAL AND SCIENTIFIC BASIS FOR INCREASING THE LIQUIDITY OF COMMERCIAL BANKS IN INVESTMENT ACTIVITIES - Jumaeva Gulrukh , Jurakulovna (THE INNOVATION ECONOMY, 2025)
This article describes the investment activity of commercial banks and its theoretical and scientific foundations, and presents scientific views, proposals and recommendations on the impact of investment activity on economic efficiency